Towards Excellence in Early Years Education : Exploring Narratives of Experience. - Goouch, Kathleen (Taylor & Francis, 2010)
This book uniquely describes the work of two Early Years Professionals, drawing on their narrative accounts as they robustly describe and analyse their work with young children. Against a backcloth of increasing regulation and inspection of early years care and education, Kathy Gooch emphasizes the importance of building authentic relationships with children and their families, explores how play can be promoted as the central site for learning, and shows how professionals can use play to account for children's development and learning. In analysing the Early Year Professionals' narratives, thi.